Development of DNA electrochemical sensor based on silicon nanowires/gold nanoparticles-modifed electrode for early detection of dengue virus - Abdul Rashid, Jahwarhar Izuan (2016)
A new DNA electrochemical sensor based on silicon nanowires (SiNWs) and gold nanoparticles (AuNPs) modified electrode was developed for dengue virus detection. In this study, two different fabricated electrodes; SiNWs/AuNPs-modified Indium tin oxide (ITO) and SiNWs/AuNPs-modified screen printed gold electrode (SPGE) have been fabricated. Field Emission Scanning Electron Microscope (FE-SEM) and Energy Dispersive X-ray Spectroscopy (EDX) analysis confirmed that the SiNWs/AuNPsnanocomposite was deposited and uniformly distribution on the surface of ITO and SPGE. Based on cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS) characterization, the fabricated SiNWs/AuNPs-ITO and SiNWs/AuNPs-SPGE have shown a good electrical conductivity compared to unmodified electrode. SiNWs/AuNPs nanocomposite was further explored as DNA matrix for DNA probe immobilization where dengue virus oligonucleotide was used as bio-sensing model to evaluate the performances of DNA electrochemical sensor. Electrochemical detection of hybridization events between immobilized DNA probe and complementary sequences of dengue virus were monitored by Different pulse voltammetry (DPV) technique using methylene blue (MB) as a redox indicator. The decrease of MB peak current was obtained after hybridization detection by both fabricated electrodes. The optimal performance of SiNWs/AuNPs-ITO and SiNWs/AuNPs-SPGE for electrochemical detection of dengue virus were obtained using response surface methodology (RSM): SiNWs volume (10.8 μL and 6 μL), dithiopropionic acid (DTPA) (0.52 mM and 0.45 μL), AuNPs volume (83 μL and 29 μL), DNA probe concentration (5.8 μM and 5 μM), immobilization time (14 hours and 10 hours), pH buffer (7.5 and 7.8), NaCl concentration (1.45 M and 0.80 M), hybridization temperature (45 °C and 42 °C) and incubation time (12 min and 10 min), respectively. Under optimized condition, developed DNA sensor showed a higher sensitivity of oligonucleotide detection as compared to the non-optimized condition. It was shown that the developed DNA sensors; SiNWs/AuNPs-ITO and SiNWs/AuNPs- SPGE were able to detect complementary oligonucleotide dengue virus as low as 0.0891 ng/μL (10 pM) and 0.0000891 ng/μL (10 fM), respectively. The stability studies also have shown that fabricated ssDNA/AuNPs/SiNWs-ITO and the ssDNA/AuNPs/SiNWs-SPGE could be stored at 4 °C for 10 weeks and 7 weeks, respectively. It was found that the MB current signal of both developed DNA sensors have increased after the hybridization of immobilized DNA probe with genomic dengue virus from cell culture samples. However, this finding was unclear to justify the ability of both developed DNA sensor for direct detection of genomic dengue virus because of MB binding interaction issue and high non-specific hybridization for long genomic sequences. Hence, the preparation of specific and amplified target genomic dengue virus using reverse-transcribe-polymerase chain reaction (RT-PCR) were investigated. The parameters of annealing temperature, sonication time and reverseforward (R/F) primer ratio using RT-PCR methods have been studied. Both developed DNA sensors are capable to discriminate the MB signal of blank electrode, negative serum samples, dengue 1 and 2 –spiked serum, cell culture and negative control. The LOD obtained for RT-PCR products value were 5.6 ng/μL and 2.8 ng/μL for SiNWs/AuNPs-ITO and SiNWs/AuNPs-SPGE, respectively. Furthermore, the developed DNA sensors; SiNWs/AuNPs-ITO and SiNWs/AuNPs-SPGE showed good reproducibility for nine measurements where the RSD value of 9.34 % and 8.23 % were obtained, respectively.